The host [videorecording (DVD)] - Pong, Chun-ho, 1969-; Song, Kang-ho, 1967-; Byun, Hee-bong; Park, Hae-il, 1977- (Magnolia Home Entertainment, 2007)
A young girl's family tries to rescue her from a monster living in the Han River.